A look through Latin America truck drivers' health, a systematic review and meta-analysis - Silvia Veridiana Zamparoni Victorino; Fernanda Silva Oliveira; Vlaudimir Dias Marques; Constanza Pujals; Mariá Romanio Bitencourt; Ana Carolina Jacinto Alarcão; Thais Silva Santos; Mariana Teixeira da Silva; Fernando Castilho Pelloso; Wagner Sebastião Salvarani; Paulo Acácio Egger; Patrícia Costa Mincoff Barbanti; et al. (BMC, 2023)
Abstract Heavy truck drivers represent a social group of great importance to any country's economy. Their professional activity requires a high level of dedication. Due to the irregular hours in their work routine and adopted habits, they mostly predispose them to a diversity of health problems. The purpose of this study is to perform a systematic review and meta-analysis aiming to identify the prevalence of diabetes, hypertension, and obesity in Latin American Truck Drivers. We searched the PubMed, Web of Science, Scopus and LILACS databases, for scientific publications articles, as reported by The PRISMA Statement. From 1,382, 7 studies were included according to the established criteria. The hypertension prevalence found was 34.2%, diabetes was of 9.2% and the highest prevalence found was for overweight and obesity (56%). Meta-analysis presented that drivers have a higher prevalence of overweight or obesity when compared to eutrophic individuals and that drivers with diabetes and hyperglycemia have a lower prevalence. Due to their work activity, their access to the health system is compromised limiting any type of monitoring of their health. This study showed that there is, in Latin America, an investment and assistance gap, both in the health sector and in the research section, for this professional category, which is so important to the economy of these countries. These data should help to identify the difficulties faced by this professional in health assistance, road safety, public safety, leisure and social life. This research also highlighted that they are young and already have the first sign of non-transmissible chronic diseases, which is overweight and obesity.